The influence of green marketing and attitude on purchase decisions of msme products with brand image as mediation - Aryani Sairun; Amril Amril; Misnanto Misnanto (Enrichment : Journal of Management, 2023)
This research is based on the importance of Green Marketing and Attitude to Purchase Decisions for MSME Products. Problem One form of consumer demand is the desire for health due to the increasing spread of diseases transmitted through food, therefore food producers produce products that contain healthy organic food ingredients, do not contain additional chemicals and are safe for consumption. The aim of the research is to analyze the influence of green marketing and attitude on purchasing decisions for MSME products with brand image as a mediator. The method of analysis of this research is quantitative research. The design of this research uses a cross sectional design method with a sampling technique using purposive sampling. This study uses data analysis with the Partial Least Square (PLS) approach. The research results of green marketing and attitude do not influence purchasing decisions, brand image is unable to moderate green marketing and attitude towards purchasing decisions and brand image influences purchasing decisions.